Pemanfaatan Pupuk Guano dalam Sistem Pertanian Berkelanjutan dan Dampaknya pada Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays saccharata L) - Lukman, Lukman (Jurnal Ilmu Pertanian Indonesia, 2022)
Guano can be used as an organic fertilizer in anticipating fertilizer shortages. This study aims to obtain the right dose of guano for the growth and yield of sweet corn (Zea mays saccharata L). The method used in this study was a single-factor randomized block design, consisting of 4 treatments of doses of guano fertilizer and 4 replications. Fertilizer dosage treatments were: g0 = no guano, g1 = 3 tons guano/ha, g2 = 5 tons guano/ha, g3 = 7 tons guano/ha. Observation parameters consisted of plant height (cm), the number of leaves (strand), the diameter of the stem (cm), the diameter of the ear (cm), the length of the ear (cm), and the weight of fruit/bed (kg). The results showed that the use of guano at a dose of 7 tons/ha was the best dose for plant height, the number of leaves, ear diameter, stem diameter, and cob weight. It was concluded that guano could increase the growth and yield of sweet corn. Keywords: corn, guano, organic fertilizer